Induction of labour at 39 weeks versus expectant management in low-risk obese women: study protocol for a randomised controlled study. Issue 4 (25th April 2022) - Krogh, Lise Qvirin; Boie, Sidsel; Henriksen, Tine Brink; Thornton, Jim; Fuglsang, Jens; Glavind, Julie
Abstract : Introduction: Obesity is associated with many pregnancy complications, including both fetal macrosomia and prolonged labour. As a result, there is often also an increased risk of caesarean section. In other settings, labour induction near to term reduces adverse outcomes such as stillbirth and birth injury, without causing more caesarean deliveries. It has been suggested that induction will reduce adverse events in this setting too, but there have been no trials and the effect on caesarean section is unknown. The objective of this study is to compare induction of labour in gestational week 39 with expectant management on the risk of caesarean section in women with body mass index ≥30 kg/m 2 . Methods and analysis: An open label randomised controlled multicentre trial are conducted at Danish delivery departments with an in-house neonatal intensive care unit. Recruitment started October 2020. A total of 1900 women with a prepregnancy body mass index ≥30 kg/m 2 are randomised in a 1:1 ratio to either labour induction at 39 weeks and 0 to 3 days of gestation or to expectant management; that is, waiting for spontaneous labour onset or induction if medically indicated. The primary outcome is caesarean section. Data will be analysed according to intention-to-treat. Ethics and dissemination: The Central Denmark Region Committee on Biomedical Research Ethics approved the study. The study is conducted in accordance with the ethical principles outlined in the latest version of the 'Declaration of Helsinki' and the 'Guideline for Good Clinical Practice' related to experiments on humans. The trial findings will be disseminated to participants, clinicians, commissioning groups and via peer-reviewed publications. Trial registration number: NCT04603859 .